Design and prototyping a peristaltic pump - Mohd Firdaus, Mansor (2008)
The main objective for this research is to design and develop a rotary peristaltic pump. This type of pump is hard to find on the market and also very rare. However, this pump has a wide application in medical sector. In order to prototype a peristaltic pump, its basic concept and function must be understand. The scope of this research are to design the pump for fabrication and determining the component that will be apply on the pump. Then engineering analysis and testing is done on the prototype to test its functionality. This prototype was successfully prototype with all the systematics plans and procedures. This prototype weight is 4 kiliograms, long 25 cm, height 22.5 cm and width 18 cm. This project basically use mild steel angle bar and aluminium and powered by an electric motor. Improvement to the part of the pump like housing and motor are recommended for further stage of the study.